Trust Busting: The Effect of Fraud on Investor Behavior - Gurun, Umit G.; Stoffman, Noah; Yonker, Scott E. (Review of Financial Studies, 2018)
We study the importance of trust in the investment advisory industry by exploiting the geographic dispersion of victims of the Madoff Ponzi scheme. Residents of communities that were exposed to the fraud subsequently withdrew assets from investment advisers and increased deposits at banks. Additionally, exposed advisers were more likely to close. Advisers who provided services that can build trust, such as financial planning advice, experienced fewer withdrawals. Our evidence suggests that the trust shock was transmitted through social networks. Taken together, our results show that trust plays a critical role in the financial intermediation industry.